Digital literacy inequality and socioeconomic readiness toward sustainable development - Laila Lilik Puspitasari (Journal of Economic Resilience and Sustainable Development, 2026)
Background: Digital literacy has become a crucial foundation for achieving sustainable development in Indonesia, particularly in relation to education, economy, and technological inclusion. Despite rapid digital transformation, disparities in digital literacy across regions remain a challenge that can hinder progress toward the Sustainable Development Goals (SDGs) 2030. This study aims to examine the relationship between digital literacy and key socioeconomic factors, including education, economic capacity, and internet access, across Indonesia’s Western, Central, and Eastern regions. Methods: Using a quantitative descriptive approach, this research analyzes secondary data from official government sources for the year 2022, including the Digital Literacy Index, average years of schooling, Gross Regional Domestic Product (GRDP) per capita, and percentage of households with internet access. Findings: The findings reveal that while the Western Region records the highest digital literacy index, followed by the Eastern and Central regions, the differences are relatively small. Education, GRDP per capita, and internet access show weak direct relationships with digital literacy, indicating that quality of education, digital exposure, and access to learning opportunities play more significant roles than duration of schooling or economic wealth. Internet access correlates with regional economic strength but does not necessarily guarantee higher literacy levels, as literacy involves critical and responsible use of technology. Conclusion The study concludes that improving digital literacy in Indonesia requires an integrated approach combining equitable infrastructure, quality education, and supportive policy. Strengthening national initiatives such as the National Digital Literacy Movement (GNLD) can accelerate progress toward SDG 4 (Quality Education) and SDG 9 (Industry, Innovation, and Infrastructure). Novelty/Originality of this article: This study provides a comprehensive analysis of the relationship between digital literacy and socioeconomic readiness at the regional level in Indonesia using national datasets. It offers new insights into how education, economy, and internet access interact in shaping digital competence, highlighting that improving literacy requires more than access but it requires quality, inclusion, and collaboration.